Critical current of dense Bi-2212 round wires as a function of axial strain. (2nd February 2015) - Godeke, A; Hartman, M H C; Mentink, M G T; Jiang, J; Matras, M; Hellstrom, E E; Larbalestier, D C
Abstract: The critical current ( I c ) of dense Bi2 Sr2 CaCu2 O8+x (Bi-2212) round wires with Ag-alloy matrices was measured as a function of axial applied strain ( ), to determine whether the behavior is improved in comparison to wires with a large (30–50%) void fraction in the Bi-2212 filaments. Wires were reacted at approximately under a 1% O2 in Ar gas mixture at 100 bar pressure to densify the Bi-2212 fraction during the partial melt reaction. After measurement of the I c at 4.2 K and 5 T at Florida State University, wire sections were sent to Lawrence Berkeley National Laboratory where was measured at 4.2 K at 5 and 15 T using a U-shaped bending spring. We found that has a 0.3% wide linear reversible strain range. An unexpected result is that the width of this reversible range seems comparable to that found for porous samples reacted at only 1 bar, apparently negating an earlier plausible supposition that fuller density samples would be more resilient.